Implementasi Manajemen Mutu Terpadu di MI Swasta Islamiyah Tarbiyah Sekar Jaya-Ogan Komering Ulu - Ibrahim; Choirun Niswah; Diah Islamiyah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
This study aims to analyze integrated quality management and its relevance to the extent to which integrated quality management is implemented. This research is focused on two topics, namely, (1) Integrated quality management implementation, (2) Inhibiting and supporting factors for integrated quality management implementation. This research was conducted at the Tarbiyah Sekar Jaya Ogan Komering Ulu Private Islamic Elementary School, using a research method based on descriptive qualitative research. The informants were madrasa heads, administrative staff, teachers, parents, students, the community and this information was obtained through interviews and observation and documentation. The data analysis technique used consisted of data reduction, data presentation and drawing conclusions. In addition, the validity of the data through triangulation is used to determine the validity of the data in this study. The results of this study indicate that the implementation of integrated quality management in Madrasah Ibtidaiyah Private Islamiyah Tarbiyah Sekar Jaya Ogan Komering Ulu has been carried out or realized, but it is not optimal, it still needs to be improved, especially in the management role of the head of the madrasa who still doubles as deputy head in the fields of curriculum, student affairs, public relations and facilities and infrastructure as well as limited facilities and infrastructure such as houses of worship and halls to support teaching and learning activities, so as to produce graduates who are superior according to the vision and mission of the madrasah.